Analisis Deskriptif ISPA pada Anak dan Balita di Pulau Moti - Marhaeni Hasan; Fera The (TECHNO: JURNAL PENELITIAN, 2020)
Acute Respiratory Infection (ARI) continues to be the leading cause of death in infants and children under the age of five throughout the world. ARI is responsible for the deaths of around 3.9 million children worldwide each year. It was reported that around 40% of total deaths from ARI around the world occurred in Bangladesh, India, Indonesia, and Nepal. The results of the 2013 Basic Health Research (Riskesdas) report showed that the prevalence of ARI in Indonesia is still quite high at 25%. The highest prevalence occurred in infants (25.8%) and infants (22%). This study aims to determine the factors that influence the incidence of acute respiratory infections (ARI) in children 0-5 years on Moti Island. This study uses an observational study using a cross-sectional approach. The samples used were 100 people with an age range of 0-5 years. The data used in the form of a questionnaire. The results showed that education occupying the highest percentage was elementary school (SD) graduates, 38%, while the percentage according to employment was as follows, the highest percentage was housewives (83%), the majority of toddlers born weighing over 2500 grams (89%), complete immunization 81%, exclusive breastfeeding has also reached 76%, 81% of these toddlers live in families who have smoking habits, 79% of respondents still use fuel, 80% of parents whose environment around the house is dusty. The conclusion that can be drawn is the risk factors that most influence the incidence of ARI in infants on Moti Island are environmental factors, namely the level of occupancy density, dusty house conditions, the use of firewood as fuel for cooking, and smoking habits of family members in the house.